Go ask Ali : half-baked advice (and free lemonade) - Wentworth, Alexandra (HarperCollins Publishers, 2018)
At once endearing and hilarious, thoughtful and far-fetched, this third collection offers Ali Wentworth at her wisest and wittiest as she delivers tips, pointers, and quips on a host of life's conundrums and sticky situations, including the funny, sometimes embarrassing yet unforgettable situations that have shaped her inimitable world view as a wife, mother, actress, comedian, and all around bon vivant.